Hidup dan Pelayanan Yesus Sebagai Landasan Pendidikan Kristiani - Sarah Wassar (Sekolah Tinggi Teologi Kerusso Indonesia, 2023)
Christian education lessons are held at home, church, and school. The importance of Christian education can be seen in the life and ministry of Jesus Christ while he was on earth. The Bible is the basis of Christian education, which guides believers to know the person, life, and ministry of Jesus as a reality for the foundation of Christian education so that Christians can carry out the task of the great commission of the Lord Jesus, (Matt. 28: 19-20) namely to make disciples of all nations and teach them to do everything that the Lord Jesus commanded. This research was conducted using qualitative methods, namely library or literature study in the form of theological analysis as a basis for conducting biblical Christian education learning. AbstrakPembelajaran pendidikan kristiani diadakan di rumah, gereja dan sekolah. Pentingnya pendidikan kristiani terlihat dalam hidup dan pelayanan Yesus Kristus selamam Ia berada di bumi. Alkitab sebagai dasar Pendidikan kristiani yang menuntun orang percaya untuk mengenal pribadi, hidup dan pelayanan Yesus sebagai realita bagi landasan pendidikan kristiani, sehingga orang Kristen dapat melakukan tugas amanat agung Tuhan Yesus, (Mat. 28: 19-20) yaitu untuk menjadikan segala bangsa murid dan ajarlah mereka untuk melakukan segala sesuatu yang Tuhan Yesus perintahkan. Penelitian ini dilakukan dengan menggunakan metode kualitatif yaitu studi pustaka atau literatur dalam bentuk analisis teologi sebagai dasar dalam melakukan pembelajaran pendidikan kristiani yang alkitabiah.